Additive metal printing on multi materials using an atmospheric pressure plasma jet on a 5-Axis platform - Oliver S.J. Hagger; Michael A. Parkes; Francis Lockwood Estrin; Stefanos Agrotis; Ivan P. Parkin; Albertus D. Handoko; Daren J. Caruana (Materials & Design)
Post-production embellishment of confromal objects with metal tracks presents significant challenges, due to the need for multiple processing steps and the complexity of navigating intricate substrate geometries. Here we describe a flexible approach to deposit conducting metal tracks on 3D objects using an atmospheric pressure plasma jet (APPJ). APPJs offer distinct advantages over traditional inkjet printing methods as they do not require metal particle inks or post-processing. An in-house-built APPJ print head was mounted onto a 5-axis platform to demonstrate metal printing on multifaceted metal, ceramic and glass complex objects. We use finite element modelling of the flow characteristics at the jet nozzle exit to understand and predict the track deposition. The modelling was corroborated through Schlieren imaging of the gas flow as well as chemical and physical characterisation of the resulting deposited track. Conductive metallic tracks of 0.3 mm widths were deposited on non-planar surfaces with one pass at a rate of 1 mm/s, using simple aqueous metal salts with an average plasma power of 10 W. Our findings reveal conductivity, adhesion strength and precision which present a benefit for additive manufacturing.